The influence of student’s multiple intelligences and the learning strategies they use in the english language learning. case: 7th, 8th and 9th graders of the instituto Técnico de Exalumnos Salesianos, year 2018 - Munguía Valencia, Claudia Verónica
The present research paper was aimed to discover the influence of the Multiple Intelligences and the Learning Strategies in the English language learning process. With the purpose of doing so, the researchers placed their attention on the English class students from the 7th, 8th, and 9th grades of the Instituto de Exalumnos Salesianos (from now on referred to as EXSAL), year 2018. During the course of this research, the research team dedicated themselves to the investigation of the uses and influence of the Multiple Intelligences Theory, originally proposed by Dr. Howard Gardner, and to discover the benefits of the correct utilization of the Language Learning Strategies, in order to find out how this two could influence the good acquisition of the English language.